PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA KANTOR PENGADILAN AGAMA KABUPATEN SITUBONDO - Hardjono Hardjono; Uswatun Hasanah (Relawan Jurnal Indonesia, 2018)
Improved employee performance can be done in order to achieve the target of excellent service for the community, namely the creation of services carried out by the government that are in accordance with standards, can also produce a positive image. The aim of this research is to determine whether variables and variables are used to determine whether the most influential variable is the variable performance of the civil company. Data collection methods were carried out by methods, interviews and questionnaires (questionnaires) at the Office of the Religious Courts of Situbondo Regency. Data analysis techniques that are multiple linear regression analysis. The results of the t-test indicate that the compensation variable (X1) partially has a significant effect on employee performance and the variable work motivation (X2) partially has a significant effect on employee performance. The results of calculations using F test (F-test) show that the compensation variable, (X1) and work motivation (X2) to operate together (simultaneously) has a significant influence on the costs of the cost of the Civil Servants at the Religious Court of Situbondo District. The results of the dominant test statistics, the work motivation variable is the most dominant on the performance of civil servants. The results of multiple linear regression analysis is Y = -2,886E-17 + 0,281 X1 + 0,593 X2 + e